2007
DOI: 10.1093/jn/137.9.2128
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Selected Nutrients Affects Bacterial Vaginosis in Women , ,3

Abstract: Bacterial vaginosis (BV), a condition of altered vaginal flora, is associated with various adverse reproductive health outcomes. We evaluated the association between diet and the presence of BV in a subset of 1521 women (86% African-American) from a larger study of vaginal flora. Participants completed the Block Food Questionnaire and clinical assessments and self-report measures of sexual and hygiene behavior. A total of 42% of the women were classified as having BV (Nugent score > or = 7). Severe BV (Nugent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 24 publications
7
104
0
7
Order By: Relevance
“…These Gram stain studies are certainly suggestive, and several groups, including ours, have ongoing genomic studies which are investigating why the vaginal microbiota fluctuate and the outcomes associated with such fluctuations. Menstrual bleeding, the hormonal fluctuation over the menstrual cycle, sexual behaviors, hygiene practices, new sexual partners, diet, and vaginal bacterial community composition are known to be contributors to fluctuation of vaginal bacterial communities based on microscopy and cultivation-based studies (63,(92)(93)(94); genomic studies will benefit the investigation of how these behavioral and extrinsic factors affect bacterial composition and abundance.…”
Section: Dynamics Of the Vaginal Microbiota: Another Layer Of Complexitymentioning
confidence: 99%
“…These Gram stain studies are certainly suggestive, and several groups, including ours, have ongoing genomic studies which are investigating why the vaginal microbiota fluctuate and the outcomes associated with such fluctuations. Menstrual bleeding, the hormonal fluctuation over the menstrual cycle, sexual behaviors, hygiene practices, new sexual partners, diet, and vaginal bacterial community composition are known to be contributors to fluctuation of vaginal bacterial communities based on microscopy and cultivation-based studies (63,(92)(93)(94); genomic studies will benefit the investigation of how these behavioral and extrinsic factors affect bacterial composition and abundance.…”
Section: Dynamics Of the Vaginal Microbiota: Another Layer Of Complexitymentioning
confidence: 99%
“…A growing body of evidence has emerged on the association between diet and nutritional status with BV (4-7), but the mechanisms remain unclear (8). Several studies have found associations between BV and poor micronutrient status, including vitamins A, C, E, and D and b-carotene (5,7) as well as low dietary intakes of folate, calcium, and vitamin E (4). LSVF previously assessed the association between macronutrient intake and BV in 1520 predominately African American women 15-44 y of age and found an increased risk of BV among women with higher energy and total fat consumption (4).…”
mentioning
confidence: 99%
“…This type of disease has been associated with lack of proper sexual orientation, education, hygiene habits, early onset of sexual activity and multiple partners [2,[8][9][10]. On the other hand, the disequilibrium in the vaginal ecosystem, due to the rise in pH above 4.5 and a decrease or absence of colonization by lactobacilli, decrease of vitamin A, folate and calcium may be predisposing factors to the proliferation of microrganismo [6,8,19].…”
Section: Discussionmentioning
confidence: 99%